Secrets of Tristan Tzara. - Heller-Roazen, Daniel (October)
The article focuses on the writer and founder of Dadaism, Tristan Tzara, and his research concerning French medieval poet François Villon. The article discusses the writing entitled "The Secret of François Villon" by Tzara which was left unpublished after his death, new information Tzara supposedly uncovered about Villon including a different birth year and a number of anagrams and axioms hidden in the writing of Villon, specifically the poem "Testament." The article goes on to discuss other scholars who continued Tzara's work including Lynn D. Stults and Michel Bernard.